DNA Data in Criminal Procedure in the European Fundamental Rights Context - Soleto, Helena (Recent Advances in DNA & Gene Sequences (Discontinued), 2014)
Despite being one of the most useful and reliable identification tools, DNA profiling in criminal procedure balances on the border between the limitation and violation of Fundamental Rights that can occur beginning with the collection of the sample, its analysis, and its use; and ending with its processing. Throughout this complex process, violation of human or fundamental rights –such as the right to physical and moral integrity, the right not to be subject to degrading treatment, the right not to incriminate oneself, the right to family privacy together with that of not incriminating descendants or relatives in general, the right to personal development and the right to informative self-determination– is possible. This article presents an analysis of all the above-mentioned DNA treating phases in criminal process in the light of possible violations of some Fundamental Rights, while at the same time discarding some of them on the basis of European human rights protection standards. As the case-law of the European Court of Human Rights shows, the legislation on DNA collection and DNA related data processing or its implementation does not always respect all human rights and should be carefully considered before its adoption and during its application.
Keywords: Criminal procedures